Pengaruh Pembelajaran Diferensiasi terhadap Hasil Belajar Mata Kuliah Bahasa Indonesia - Ratri Wikaningtyas; Ahmad Sunardi; Prasetya Nugraha (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
In the process of learning Indonesian, it is often found that each student has a different level of understanding and ability. In addition, factors such as different learning styles can also affect student learning outcomes. Differentiated learning can be influential in improving student learning outcomes. This study aims to find the effect of differentiated learning on students' grades in Indonesian language courses. This research uses quasi-experimental method. Differentiated learning has an effect on improving student learning outcomes in Indonesian language courses seen from a significant level of 0.05 the value of Fstatistic = 0.0758 and FKritis = 0.4401 which means FKritis> Fstatistic (0.4401>0.0758), so differentiated learning can affect the improvement of nursing student learning outcomes in Indonesian language courses.